IMPROVEMENTS IN COMPLEX TREATMENT OF PATHOLOGICAL CHANGES IN THE ORAL CAVITY IN PATIENTS WITH IRON DEFICIENCY ANEMIA (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The oral cavity has a close anatomical and physiological interaction with various body systems. Pathogenetically limited damage to the oral mucosa occurs when homeostasis is disturbed and in various somatic diseases. The stability of the chemical composition is one of the most important and inevitable conditions for the normal functioning of the body, and the oral mucosa can be an indicator or mirror of pathological processes occurring in general. Diseases caused by deviations in the content of chemical elements in the human body, caused by environmental, professional, climatic and geographical factors, lead to a wide range of health disorders, including the condition of the oral mucosa.